Impact of the number of previous embryo implantation failures on IVF/ICSI-ET pregnancy outcomes in patients younger than 40 years: a retrospective cohort study - Fang, Yuan; Jingjing, Fan; Tiantain, Cheng; Huanhuan, Xie; Qiaohua, He (Frontiers in Endocrinology, 2023)
Univariate logistic regression analysis demonstrated that factors such as the number of previous embryo implantation failures, female age, basal follicle count, endometrial thickness, total number of oocytes retrieved, type of cycle, number of high-quality embryos transferred, and stage of embryo development significantly affected implantation rate, clinical pregnancy rate, early spontaneous abortion rate, and live birth rate (all P < 0.05). The duration of infertility and anti-Mullerian hormone (AMH) levels were also found to influence implantation rate, clinical pregnancy rate, and live birth rate (all P < 0.05). Upon conducting multivariate logistic regression analysis and adjusting for confounding factors such as age, AMH levels, basal follicle count, endometrial thickness, total number of oocytes obtained, cycle type, number of high-quality embryos transferred, ovarian stimulation protocol, and stage of embryo development, it was revealed that, compared to Group A, Groups B, C, and D exhibited significantly lower implantation and live birth rates, as well as a significantly higher risk of early spontaneous abortion (all P < 0.05).The number of previous embryo implantation failures is an independent factor affecting implantation rate, clinical pregnancy rate, spontaneous abortion rate and live birth rate of patients underwent IVF/ICSI-ET. With the increase of the number of previous embryo implantation failures, the implantation rate, clinical pregnancy rate and live birth rate of patients underwent IVF/ICSI-ET 3 decreased significantly, and the rate of early spontaneous abortion gradually increased.